Does social media impact the development of general English vocabulary? perceptions of Egyptian university students - Amr Selim Wannas; Inas Hussein Hassan (Insights into Language, Culture and Communication)
The importance of vocabulary in language learning cannot be overstated because meaningful communication requires a vast repertoire of words to convey ideas. Yet, social media places English language learners in multicultural communities where they can acquire new vocabulary knowledge and use it communicatively. The aim of the study is to investigate the impact of social media on learning English vocabulary at university level. A case study approach was adopted. To this end, a hypothesized model on aspects of learning English from social media was constructed. That was supported by a participant observation and a thorough review of the literature. Based on the model, a questionnaire was constructed and disseminated to a total number of 135 Egyptian undergraduate university students.  Findings of the study are: 1) learning vocabulary occurs through receiving, producing and constructing vocabulary knowledge, 2) the indirect impact of social media enhances self-confidence, self-esteem, critical thinking, creativity and collaboration among Egyptian university students, 3) social media is characterized by factors that enhance vocabulary learning, and 4) social media has a few limitations that, to some extent, hinder vocabulary learning. It is recommended that further research is conducted on the effect of different social media applications on learning English language vocabulary, grammar and other aspects.   Received: 24 February 2023 Accepted: 05 March 2023 Published: 20 March 2023